X-ray characterization of ZnSe single crystals doped with Mg - Fedorov, A.G.; Zagoruiko, Yu.A.; Fedorenko, O.A.; Kovalenko, N.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Doping of cubic ZnSe with certain impurities like Mg or Mn during crystal growth causes the increased contents of the hexagonal phase in the crystal or even the transformation to hexagonal wurtzite modification that possess the anisothropy of properties. This opens the possibility to design not only the passive optical elements of this material but provide them with controlling or measuring functions. In the present work the structure evolution of ZnSe single crystals due to the Mg doping of different concentration was examined using the double crystal X-ray spectrometer.